Cloning, expression analysis and recombinant expression of a gene encoding a polygalacturonase-inhibiting protein from tobacco, Nicotiana tabacum. Issue 5 (May 2016) - Zhang, Chengsheng; Feng, Chao; Wang, Jing; Kong, Fanyu; Sun, Wenxiu; Wang, Fenglong
Abstract: Polygalacturonase inhibiting proteins (PGIPs) are major defensive proteins produced by plant cell walls that play a crucial role in pathogen resistance by reducing polygalacturonase (PG) activity. In the present study, a novel PGIP gene was isolated from tobacco ( Nicotiana tabacum ), hereafter referred as NtPGIP . A full-length NtPGIP cDNA of 1, 412 bp with a 186 bp 5′-untranslated region (UTR), and 209 bp 3′-UTR was cloned from tobacco, NtPGIP is predicted to encode a protein of 338 amino acids. The NtPGIP sequence from genomic DNA showed no introns and sequence alignments of NtPGIP 's deduced amino acid sequence showed high homology with known PGIPs from other plant species. Moreover, the putative NtPGIP protein was closely clustered with several Solanaceae PGIPs. Further, the expression profile of NtPGIP was examined in tobacco leaves following stimulation with the oomycete Phytophthora nicotianae and other stressors, including salicylic acid (SA), abscisic acid (ABA), salt, and cold treatment. The results showed that all of the treatments up-regulated the expression of NtPGIP at different times. To understand the biochemical activity of NtPGIP gene, a full-length NtPGIP cDNA sequence was subcloned into a pET28a vector and transformed into E. coli BL21 (DE3). Recombinant proteins were successfully induced by 1.0 nmol/L IPTG and the purified proteins effectively inhibited Phytophthora capsici PG activity. The results of this study suggest that NtPGIP may be a new candidate gene with properties that could be exploited in plant breeding.